NUTRITION-RUN GAME MENINGKATKAN PENGETAHUAN DAN SIKAP PENTINGNYA SAYUR DAN BUAH PADA ANAK - Azari, Hanifah; Melani, Vitria; Gifari, Nazhif; Nuzrina, Rachmanida (Poltekkes Kemenkes Semarang, 2022)
Background: The growth and development experienced by school-age children need to be supported by optimal nutritional intake, which can be obtained from vegetables and fruit. In order for these conditions to be achieved, it is necessary to provide interesting nutrition education so that children can understand well. In addition, it will form good nutritional behavior as well.Objective: To determine the effect of Nutrition-Run Game media on children's knowledge and attitudes towards the importance of consuming vegetables and fruits.Methods: This research design is Quasi-Experimental with One Group Pretest and Posttest Design. The research subjects were 37 children aged 9-12 years in the Sitanala Multipurpose Complex RT.004. The sampling technique is purposive sampling. The number of questionnaires used for knowledge is 13 questions, and attitudes are 14 questions Subjects were given a pre-test questionnaire and then given an intervention using the Nutrition-Run Game media. After that, the subject was given a post-test 1 questionnaire. Then, seven days later, the subject was again given the same questionnaire (post-test 2). Analysis of the data used is the Paired Sample T-Test.Results: The results showed that most of the subjects had a low level of knowledge (81,1%), and there were still subjects who had poor attitudes (24,3%). After being given education, there was an increase in scores for both variables. The bivariate analysis results showed a significant difference between knowledge and attitude scores before and after giving intervention media regarding the importance of consuming vegetables and fruit (p≤0,05).Conclusion: There is an effect of using the Nutrition-Run Game media on children's knowledge and attitudes regarding vegetable and fruit consumption.